2019
DOI: 10.1111/jfbc.12833
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging activity of the peptide from the Alcalase hydrolysate of the edible aquacultural seahorse ( Hippocampus abdominalis )

Abstract: Seahorses, Hippocampus abdominalis, have a long history in traditional Chinese medicine as an important healthy ingredient in foods. This study evaluated the antioxidant activity of an enzymatic hydrolysate prepared from a seahorse bred in Jeju, South Korea. Experiments were performed in vitro using electron spin resonance spectrometry (ESR) to determine the free radical scavenging activity and in vivo using a zebrafish model to determine the protective effects against 2,2‐azobis hydrochloride (AAPH)‐induced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…Among these three MW groups, the <5 kDa fraction showed the strongest peroxyl radical scavenging activity. Previous reports have found that food proteins hydrolysates can be separated into three fractions (>10 kDa, 5–10 kDa and <5 kDa) by UF according to MW and that the <5 kDa fraction exhibits the strongest free radical scavenging activity [6,17,24]. Results of the present study also demonstrated that low MW fraction of Alcalase-proteolytic hydrolysate had higher free radical scavenging activity than higher MW fractions.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Among these three MW groups, the <5 kDa fraction showed the strongest peroxyl radical scavenging activity. Previous reports have found that food proteins hydrolysates can be separated into three fractions (>10 kDa, 5–10 kDa and <5 kDa) by UF according to MW and that the <5 kDa fraction exhibits the strongest free radical scavenging activity [6,17,24]. Results of the present study also demonstrated that low MW fraction of Alcalase-proteolytic hydrolysate had higher free radical scavenging activity than higher MW fractions.…”
Section: Discussionsupporting
confidence: 75%
“…Among these hydrolysates, Alcalase-derived hydrolysate possessed the highest peroxyl radical scavenging activity. Although the trypsin hydrolysate also showed a potent peroxyl radical scavenging activity, Alcalase can produce shorter peptide sequences and terminal amino acid sequences responsible for various bioactivities as well as useful for the production of bioactive peptide [16,17,18]. Therefore, Alcalase hydrolysate was selected to identify antioxidant peptide for further studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seahorse has various biomedical benefits. Seahorse has been reported to have anti-cancer [ 20 , 21 ], antimicrobial [ 22 ], anti-rheumatism [ 23 , 24 ], anti-oxidant [ 25 , 26 ], anti-inflammation [ 27 ], benign prostatic hyperplasia alleviative [ 28 ], and neuroprotective effects [ 29 , 30 ]. The two studies for anticancer effect of seahorse showed bioactive compounds and peptide from seahorse and their anti-metastatic ability in HT 1080 human fibrosarcoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants can be received through food ingestion and/or produced within the animal's body (Castex, Pierrette, Wabete, & Chim, 2009; Hamre et al., 2016). For example, seahorses used as traditional medicine exhibited high antioxidant activity and could inhibit intracellular reactive oxygen species (Kim et al., 2019; Qian, Kang, & Kim, 2012; Yin & Tang, 2012; Zhang, Ryu, & Qian, 2017). However, the antioxidant capacity of seahorses under different culture conditions needs further evaluation.…”
Section: Introductionmentioning
confidence: 99%